Radio Wave Generation Using Dark and Bright Soliton - M.A. Jalil; A. Afroozeh; M.S. Aziz; I.N. Nawi; None J.Ali; P.P. Yupapin (My University, 2011)
In this study we propose a new system for radio wave using a soliton pulse within a micro waveguide and nano-waveguide. The system consists of two micro ring resonators and a nano ring resonator that can be integrated into a single system. The input soliton power, coupling coefficients, and ring radii, are used to control the short-wave and millimeter-wave output signals being generated and filtered in a single system. The large bandwidth signal is generated using a soliton pulse within a Kerr-type nonlinear medium. The signals with broad bandwidth or wavelength can then be generated. Results obtained have shown the potential of using this system for a broad light spectra generation.
Keywords: Extremely high frequency; Photonic and Optical Devices